An investigation of science and engineering undergraduates' motivation towards learning english in Pakistan - Siming, Insaf Ali (2016)
Attitude and motivation have been crucial elements within the context of a learning a language. Studies have shown that motivation plays a vital role in language learning. When students are motivated, their language proficiency skills are enhanced. The students with higher level of motivation will do better than those with lower level of motivation. Thus, the present study was conducted to investigate the reasons for learning English in Pakistan particularly the most dominating types of motivation namely instrumental motivation or integrative motivation. Besides that the study investigated the most influencing factors that affect the learners’ motivation. Finally, the current study has drawn a comparison between science and engineering students at research venue. A cross-sectional approach was adopted to inspect the types of motivation and most influential factors among the science and engineering students by using both quantitative and qualitative methods. The data was collected from 480 respondents at one point before the end of an English course at Quaid-e-Awam University of Engineering Science and Technology in Pakistan. For a clearer picture of the study, 18 students were interviewed to cross validate findings obtained through questionnaires. The findings of the study revealed that Pakistani science and engineering students learn English for both instrumental and integrative orientation but the instrumental orientation dominated over integrative orientation. In addition, engineering students were significantly more motivated than science students over 10 factors. 12 hypotheses were developed and tested; the findings showed that 10 hypotheses were accepted while 2 were rejected. Further, the open-ended responses revealed that the mother tongue of respondents does not play any pivotal role for learning English. Moreover, the results revealed that the Pakistani students who were engaged in student politics, their role for learning English remained as neutral or negative. The students in general were enthusiastic to learn English. The findings of the present study may be fruitful for researchers, educationist, and course designer todesign strategies and syllabus that could help learners in future.